Repression of Mitochondrial Citrate Synthase Genes by Aluminum Stress in Roots of Secale cereale and Brachypodium distachyon - Abd El-Moneim, Diaa; Contreras, Roberto; Silva-Navas, Javier; Gallego, Francisco Javier; Figueiras, Ana M.; Benito, Cesar (Frontiers in Plant Science, 2022)
Aluminum toxicity in acid soils has an effect on plant development and yield. Almost 50% of arable land is acidic. Plants have evolved a variety of tolerance mechanisms for Al. In response to the presence of Al, various species exudate citrate from their roots. Rye (Secale cereale L.) secretes both citrate and malate, making it one of the most Al-tolerant cereal crops. However, no research has been done on the role of the mitochondrial citrate synthase (mCS) gene in Al-induced stress in rye. We have isolated a mCS gene, encoding a mitochondrial CS isozyme, in two S. cereale cultivars (Al-tolerant cv. Ailés and Al-sensitive inbred rye line Riodeva; ScCS4) and in other two Brachypodium distachyon lines (Al-tolerant ABR8 line and Al-sensitive ABR1 line; BdCS4). Both mCS4 genes have 19 exons and 18 introns. The ScCS4 gene was located on the 6RL rye chromosome arm. Phylogenetic studies using cDNA and protein sequences have shown that the ScCS4 gene and their ScCS protein are orthologous to mCS genes and CS proteins of different Poaceae plants. Expression studies of the ScCS4 and BdSC4 genes show that the amount of their corresponding mRNAs in the roots is higher than in the leaves and that the amounts of mRNAs in plants treated and not treated with Al were higher in the Al-tolerant than in the Al-sensitive lines of both species. In addition, the levels of ScCS4 and BdCS4 mRNAs were reduced in response to Al (repressive behaviour) in the roots of the tolerant and sensitive lines of S. cereale and B. distachyon.